Analisis Kualitas Air Pada Sistem Budidaya Ikan Nila (Oreocromis nilotius) di Balai Benih Ikan Andalas, Kota Gorontalo - Lamangkaraka, Rezki Rahmatian; Mulis, Mulis; Koniyo, Yuniarti; Alvionita, Mita (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
This research aims to determine water quality analysis in different cultivation systems for tilapia (Orecromis niloticus) cultivation. This research was carried out in May 2024 at the Andalas Fish Seed Center, Gorontalo City. Method: This data was obtained from the results of measurements in the Bioflok pond, which is a holding pond for Tilapia fish (Oreocromis niloticus) and the Beton pond, which is a pond for rearing Tilapia fish seeds (Oreocromis niloticus), where measurements of pH, DO and temperature are carried out every 6 hours and on measurements. Table media is used in data processing to differentiate between one result and another. Based on the research results, it shows that the cultivation system using biofloc ponds is more effective in converting ammonia compounds into nitrate compounds and maintaining the water quality of the tilapia cultivation media. Water quality greatly influences the growth and survival of farmed fish, where biofloc ponds with more controlled water quality can increase the growth and survival of farmed fish.